Cathode Positioning System for Multiple Beam Electron Gun - Sinkevicius, V.; Virzonis, D.; Sumskiene, L.; Jukna, T. (Elektronika ir Elektrotechnika, 2006)
The results of the investigations of the dual-stage cathode positioning system with more than 150 mm motion range and ±1 μm positioning accuracy are presented. The maximum allowable speed of the second stage actuator, securing the integrity of the cathode surface, of 10 mm/s was determined experimentally. The dynamic model of the cathode-probe system allowed to explore the dynamics of the interaction force and the dependencies of their character on the viscous friction. Ill. 6, bibl. 6 (in English; summaries in English, Russian and Lithuanian).